EDUKASI PENGELOLAAN SAMPAH RUMAH TANGGA - Nurmalasari, Auliya; Cahyo, Septian Dwi (ICON Publisher, 2025)
Household waste management is an important issue that needs attention in the community, especially in Bendosari-Tegalrejo Village, Yogyakarta. The aim of this community service is to educate residents on proper waste management practices to enable them to utilize waste that has economic value. The method used for this activity involves lectures and interactive discussions, engaging local PKK members. The analysis technique applied includes observation and evaluation of participants' understanding before and after the education. Results indicate an increase in community awareness regarding the importance of waste sorting and the utilization of sellable waste. Participants expressed high enthusiasm during discussions and reached an agreement to implement waste sorting in their environment. Thus, this activity is expected to positively impact the community's awareness of waste management.